Association of monocyte to high-density lipoprotein cholesterol ratio with carotid artery intima-media thickness in patients with systemic lupus erythematosus. (April 2018) - Wang, Qian; Meng, Yan; Cao, Wenyan; Du, Wenjing; Liu, Yumei; Yan, Yi; Luo, Li; Ma, Xiumin
Aim: The purpose of this study was to evaluate the relationship between monocyte to high-density lipoprotein cholesterol ratio (MHR) and carotid atherosclerostic plaque in patients with systemic lupus erythematosus (SLE).Methods: A total of 214 SLE patients were divided into two groups according to the results of ultrasonic examination: carotid arterial atherosclerotic plaque groups and noncarotid arterial atherosclerosis groups.Results: The values of monocyte to high-density lipoprotein-cholesterol ratio (MHR) increase in carotid arterial atherosclerotic plaque groups compared with noncarotid arterial atherosclerosis groups (0.32 ± 0.18 vs 0.26 ± 0.15; p = 0.015). There was a significant correlation between MHR and carotid artery intima-media thickness (r = 0.228; p = 0.001) in patients with SLE.Conclusion: Our study suggests that the values of MHR could be a marker to assess carotid artery intima-media thickness in patients with SLE.